2020
DOI: 10.7759/cureus.11746
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes After Treatment of Posterior Inferior Cerebellar Artery Aneurysms

Abstract: Aneurysms of the posterior inferior cerebellar artery (PICA) are a rare cause of subarachnoid hemorrhage. Treatment for this type of aneurysm may be microsurgical clipping or endovascular. This decision is based on patient characteristics, aneurysm location and dimensions, along with surgeon and institutional experience. In this study we aim to assess the outcomes of surgical and endovascular treatment of PICA aneurysms. Methods We retrospectively reviewed the charts of 52 patients who were admitted to Vancouv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Surgical treatment of PICA aneurysms can achieve good results (tables 1 and 2) and the individualised surgical strategy varies according to the aneurysm’s segmental location and morphology (figure 1). 14 16 18 32 39 However, although DSA remains the gold standard for aneurysm diagnosis and angioarchitecture assessment, it does not provide the aneurysmal wall structure data that HR-VW MRI does 17. We found a significant difference between DSA and HR-VW MRI aneurysm size measurements, with MRI arriving at a larger size.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Surgical treatment of PICA aneurysms can achieve good results (tables 1 and 2) and the individualised surgical strategy varies according to the aneurysm’s segmental location and morphology (figure 1). 14 16 18 32 39 However, although DSA remains the gold standard for aneurysm diagnosis and angioarchitecture assessment, it does not provide the aneurysmal wall structure data that HR-VW MRI does 17. We found a significant difference between DSA and HR-VW MRI aneurysm size measurements, with MRI arriving at a larger size.…”
Section: Discussionmentioning
confidence: 66%
“…After aneurysm exposure and inspection, direct clipping or clip reconstruction was preferentially performed. If the aneurysm was unclippable due to complexity, bypass and trapping was considered, especially for proximal aneurysms associated with critical brainstem perforators 1 5 9 11–14 18 20 22–24 26 29 32–38. We preferred intracranial–intracranial (IC-IC) bypass over extracranial–intracranial (EC-IC) bypass when possible.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, the surgical management of PICA aneurysms carries a high risk, regardless of whether the patient has ischemia or SAH. 8,9 Endovascular therapy of PICA aneurysms has resulted in more favorable outcome because of the lower risk in injuring neighboring lower cranial nerves as well as the PICA perforating branches. Coil embolization is still the preferred treatment option for narrow-necked saccular aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded no significant difference in outcomes between the microsurgical and endovascular treatment groups at short- and long-term follow-ups. 32 Del Maestro et al reported 25 (60% rupture) patients with PICA aneurysms treated with microsurgery (92% by direct clipping and 8% by PICA–PICA bypass with trapping) via the far-lateral approach, and 60% of the patients achieved good outcomes. 33 …”
Section: Discussionmentioning
confidence: 99%